2012
DOI: 10.1177/089875641202900105
|View full text |Cite
|
Sign up to set email alerts
|

Cone Beam Computed Tomography in Veterinary Dentistry

Abstract: The purpose of this study was to assess the feasibility of cone beam computed tomography (CBCT) in imaging dogs and cats for diagnostic dental veterinary applications. CBCT scans of heads of six dogs and two cats were made. Dental panoramic and multi-planar reformatted (MPR) para-sagittal reconstructions were created using specialized software. Image quality and visibility of anatomical landmarks were subjectively assessed by two observers. Good image quality was obtained for the MPR para-sagittal reconstructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…Authors suggested that the moderate image quality obtained with the CBCT technique seemed to be inferior to the diagnostic image quality obtained from 2-dimensional dental radiographs. 14 Analogous to our findings, authors found CBCT to perform very good for the assessment of dentomaxillofacial structures and periodontal disease. 15,16 We obtained high-quality and high-definition images of rat teeth.…”
Section: Discussionsupporting
confidence: 87%
“…Authors suggested that the moderate image quality obtained with the CBCT technique seemed to be inferior to the diagnostic image quality obtained from 2-dimensional dental radiographs. 14 Analogous to our findings, authors found CBCT to perform very good for the assessment of dentomaxillofacial structures and periodontal disease. 15,16 We obtained high-quality and high-definition images of rat teeth.…”
Section: Discussionsupporting
confidence: 87%
“…61,65,78 Recently, adaption of cone-beam CT for panoramic and parasagittal reconstructions in dogs and cats was found to be inferior to conventional dental radiography however the study did not evaluate the diagnostic value of cone-beam CT in relation to apical periodontitis. 106 In one study, cone-beam CT was found to have a sensitivity (proportion of positives correctly identified) of 0.91, specificity (proportion of negatives correctly identified) of 1, positive predictive value (the likelihood that a positive result is true) of 1, a negative predictive value (the likelihood that a negative result is true) of 0.46, and an accuracy (the proportion of true positives and true negatives identified) of 0.92. By comparison periapical radiography was found to have a sensitivity of 0.77, specificity of 1, a positive predictive value of 1, a negative predictive value of 0.25 and an accuracy of 0.78.…”
Section: Figurementioning
confidence: 99%
“…Computed tomography can be used to obtain more detailed imaging information for fracture evaluation in dogs and cats. [7][8][9] Micro-CT involves use of a microfocal source (range in slice thickness, 30 to 150 µm), and 2-D or 3-D spatial resolution is possible independent of patient body position. 5,6 However, CT cannot be used to detect small orthopedic lesions in smaller companion animal species such as rodents and rabbits, and the need for anesthesia to keep patients motionless during the scanning process makes CT even less suitable for these species.…”
mentioning
confidence: 99%